Chapter Unione per mezzo della democrazia - Guarnieri, Ivanor Luiz (Libere carte, 2023)
This article brings an implicit problem: How to unite different peoples and cultures, that are in constant tranformation, around a commom project? The democratic regime is the most approprieate for this task, as it respects diferences and combines it with freedom and justice to promote equal opportunities. On the other hand, the union carried out democratically improves democracy, both favoring each other.